An Event History Analysis of Latin American Migrant Couples - Gómez-Gómez, Maite Michell; Silva-Arias, Adriana Carolina; Sarmiento-Espinel, Jaime Andrés (Sociedad y Economía, 2021)
The purpose of this paper was to study the association between migration and reproductive decisions in Mexico, Costa Rica, the Dominican Republic, Ecuador, Guatemala, and Colombia. An event history analysis was used to study the fertility and migration decisions made by a sample of couples from those countries. This study found a disruption in fertility before migrating. After the migration event and settlement, fertility increased to the same levels as the place of origin for migrants who stayed longer at their destination, particularly for those who migrated to the United States. Couples in which only the man migrated had a higher migratory prevalence. These men were young and had low human capital. Although the proportion of couples in which both members migrated was low, those couples stayed longer at their destination and their fertility disruption before migrating was highest.